The Negro migration / by Monroe N. Work. - Work, Monroe Nathan, author. (Tufts University. Tisch Library., 2019)
[United States] : [publisher not identified], [1924?]; 1 online resource (15 pages); Reprinted from the "Southern workman" for May 1924.; Includes bibliographical references (pages 14-15).